Evaluation of ten courses from the major in Pharmacy based on a curricular perspective - Acuña Rodríguez, María del Carmen (Universidad de Costa Rica, 2012)
Quality of courses is an interesting subject for many professors at the Faculties or Schools of the University of Costa Rica. The decision to improve courses requires information from students and professors as well as information from academic performance results. The present article gathers the results of the evaluation of ten courses from the major in Pharmacy of the University of Costa Rica. Results reflect that there is no relationship between the professional profile of the major and the didactic activities used in the evaluated courses. In other words, this evaluation reflects that changes must be done in the courses in order to put into practice pedagogical-oriented ideas, such as critical and creative thinking, decision making, problem research, and problem solution.